2005
DOI: 10.1258/rsmvasc.13.6.321
|View full text |Cite
|
Sign up to set email alerts
|

Aorfix Stent Graft for Abdominal Aortic Aneurysms Reduces the Risk of Proximal Type 1 Endoleak in Angulated Necks: Bench-Test Study

Abstract: Neck angulation (NA) is an important risk factor for type 1 proximal endoleaks following stenting of abdominal aortic aneurysms. The Aorfix (Lombard Medical, Oxon, UK) is a new flexible stent graft designed to overcome this issue. The aim of this study was to compare the endoleak flow rate (EFR) in relation to NA between the Aorfix and other manufactured stent grafts. A flow model with silicone proximal and distal necks was used. EFRs corresponding to 10 neck angles between 0 and 70 degrees were measured. Eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Increasing aortic neck angulation has been shown to increase perigraft endoleak flow, thereby leading to poor seal and graft separation. 6,7 Consistent with this notion, severe aortic neck angulation has been associated with worse outcomes after EVAR in multiple prior studies. 8 In a prospective study of 81 EVAR repairs by Sternbergh et al, patients with severely angulated aortic necks had a 70% risk of experiencing one or more adverse events (including death within 30 days, acute conversion to open repair, aneurysm expansion, device migration, and type I endoleak) compared with a 17% risk in patients with mild (<40-degree) aortic neck angulation.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Increasing aortic neck angulation has been shown to increase perigraft endoleak flow, thereby leading to poor seal and graft separation. 6,7 Consistent with this notion, severe aortic neck angulation has been associated with worse outcomes after EVAR in multiple prior studies. 8 In a prospective study of 81 EVAR repairs by Sternbergh et al, patients with severely angulated aortic necks had a 70% risk of experiencing one or more adverse events (including death within 30 days, acute conversion to open repair, aneurysm expansion, device migration, and type I endoleak) compared with a 17% risk in patients with mild (<40-degree) aortic neck angulation.…”
mentioning
confidence: 61%
“…These favorable results are likely due to the flexibility of the graft construction. In a bench study comparing existing aortic endografts, aortic neck angles $30 degrees caused a significant increase in endoleak flow rate in seven manufactured models ( 7 In contrast, neck angulation had no influence on the endoleak flow rate of the Aorfix. In a computational model comparing flexibility of the Aorfix with the Zenith stent grafts, the Aorfix graft performed better with respect to maximal luminal reduction rate, torque, strain, and stress for aortic neck angulation >60 degrees.…”
Section: Discussionmentioning
confidence: 99%
“…Angulation of proximal and distal aneurysm necks is a well‐established predictive factor of adverse events following EVAR, particularly type 1 endoleaks . Bench test studies have shown that inadequate SG apposition on the arterial wall was a mechanism for type 1 endoleaks . Therefore, the results of the present simulation are relevant to the above‐mentioned clinical complications.…”
Section: Discussionmentioning
confidence: 84%
“…Endoleaks and stent-graft (SG) limb thrombosis are among the most frequent causes of secondary interventions following EVAR. Endoleaks may be associated with incomplete SG apposition on the arterial wall (Albertini et al, 2001(Albertini et al, , 2005. Graft kinking has been proved to favor stenosis and thrombosis (Carroccio et al, 2002;Cochennec et al, 2007).…”
Section: Introductionmentioning
confidence: 99%